A Comparison and Prediction of Irrational Beliefs and Cognitive Functioning Among Depressed and Non-Depressed Adults in Gujrat, Pakistan - Naz, Iram; Ahmed, Laiba; Ishaq, Amna; Ayyaz, Maryyam (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare and predict the irrational beliefs and cognitive functioning among depressed and non-depressed adults in Gujrat, Pakistan. Study Design: Comparative cross-sectional study. Place and Duration of Study: Zulfiqar Hospital, Akram Hospital and Aziz Bhatti Hospital, Gujrat and Department of Psychology, the University of Gujrat from Dec 2017 to Mar 2018. Methodology: The data was collected from 200 adults, 100 depressed adults and 100 non-depressed adults using consecutive sampling. The non-depressed adults with no past psychiatric history were recruited from the community. The irrational beliefs were assessed using the Evaluative beliefs scale, and cognitive functioning was measured using the Montreal cognitive assessment scale. Results: The independent sample t-test indicated that there was a statistically significant difference (p<0.001) in the irrational beliefs of depressed and non-depressed adults, and the irrational beliefs of depressed were more (37.83 ± 8.12) than the nondepressed adults (4.33 ± 4.64). The comparison of cognitive functioning of the depressed and non-depressed was also significantly different (p<0.001). The cognitive functioning of depressed adults was poorer (12.44 ± 3.85) than the nondepressed adults (26.92 ± 2.55). Further-more, irrational beliefs predict cognitive functioning [R²=0.729; F (1,198) = 532.763, p<0.001]. Conclusion: The study findings indicated a difference in the irrational beliefs and cognitive functioning of depressed and nondepressed adults. Further, the depressed had more irrational beliefs and worsened cognitive functioning.